ANALISIS KEBIJAKAN SUBSIDI PUPUK : PENENTUAN POLA SUBSIDI DAN SISTEM DISTRIBUSI PUPUK DI INDONESIA - Dudi S. Hendrawan; Arief Daryanto; Bunasor Sanim; Hermanto Siregar (Jurnal Manajemen & Agribisnis, 2011)
This study aims to determine an alternative subsidy model and distribution system of fertilizer in Indonesia. The purpose of the research in details are to create a framework of fertilizer subsidy policy, analyze factors that are affecting the fertilizer subsidy policy, and to select the best alternative subsidy model and distribution system of fertilizer. Analitical methods used to answer these purposes is by using the Analytic Network Process (ANP) which is also supported by literature study, focus group discussions and interviews with expert respondents. The result concludes that the conditions that affect fertilizer subsidy policy is the economic condition, The main priority of the fertilizer subsidy objective is availibility of fertilizer, the most prioritized fertilizer subsidy is the subsidy for inorganic fertilizer, Ministry of agriculture is the most important actors in the implementation of the fertilizer subsidy policy, and the most important factor considered in choosing a fertilizer distribution system is supervision. The choice of fertilizer subsidy policy in Indonesia is the indirect subsidy model through the manufacturer and its distribution system is conducted by the manufacturer to the farmer.   Keywords : Subsidy Policy, Fertilizer Subsidy, Fertilizer Distribution, ANP